A novel potential therapeutic avenue for autism: Design, synthesis and pharmacophore generation of SSRIs with dual action - Ghoneim, Ola M.; Ibrahim, Diaa A.; El-Deeb, Ibrahim M.; Lee, So Ha; Booth, Raymond G. (Pergamon Press Ltd., 2011)
Autism symptoms are currently modulated by Selective Serotonin Reuptake Inhibitors (SSRIs). SSRIs slow onset of action limits their efficiency. The established synergistic activity of SSRIs and 5HT(1B/1D) autoreceptors antagonists motivated us to incorporate SSRIs and 5HT(1B/1D) antagonists in one 'hybrid' molecule. A library of virtual 'hybrid' molecules was designed using the tethering technique. A pharmacophore model was generated derived from 16 structurally diverse SSRIs (K-i = 0.013-5000 nM) and used as 3D query. Compounds with fit values (>= 2) were chosen for synthesis and subsequent in vitro biological evaluation. Our pharmacophore model is a promising milestone to a class of SSRIs with dual action. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: SEROTONIN REUPTAKE INHIBITORS; BIOLOGICAL EVALUATION; RECEPTOR; DERIVATIVES; ANTAGONISTS; PIPERAZINES; DISRUPTION; ACTIVATION